2023
DOI: 10.31219/osf.io/jn3v6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The over-prediction of energy use by EPCs in Great Britain: A comparison of EPC-modelled and metered primary energy use intensity

Abstract: This analysis compares the difference between the Energy Performance Certificate (EPC)-modelled and smart meter measured annual energy use on a like-for-like basis in 1,374 gas-heated British households selected from the Smart Energy Research Lab (SERL) Observatory. EPCs and metered energy use were converted to primary energy use intensity to provide a comparison of the same quantity for the first time.We show that EPCs predict substantially and significantly more energy use than metered in homes in Great Brit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We would expect to see a stronger trend in the gas analysis, as heating requirements should be more strongly related to EPC rating. That said, recent analysis has shown that the energy use in EPC bands C, D, F and G typically do not reflect the energy use predicted by EPCs, and the average energy use between these bands is very similar [33]. Figure 7 reveals that dwellings in bands D-G increased gas use by more than those in bands B and C during October 2020 -March 2021 (including the winter lockdowns).…”
Section: Energy Performance Certificatementioning
confidence: 90%
See 2 more Smart Citations
“…We would expect to see a stronger trend in the gas analysis, as heating requirements should be more strongly related to EPC rating. That said, recent analysis has shown that the energy use in EPC bands C, D, F and G typically do not reflect the energy use predicted by EPCs, and the average energy use between these bands is very similar [33]. Figure 7 reveals that dwellings in bands D-G increased gas use by more than those in bands B and C during October 2020 -March 2021 (including the winter lockdowns).…”
Section: Energy Performance Certificatementioning
confidence: 90%
“…For both fuels, around half had an Energy Performance Certificate (EPC), among which the most and least efficient dwellings are overrepresented in our samples. Recent evidence suggests that the EPC provides a good indication of actual energy use for the most efficient bands (A and B), but not for all other bands [33]. Thus, the overrepresentation of the most efficient bands is likely to mean that there are more efficient homes in the sample than expected, but the over-representation of homes in less efficient EPC bands does not necessarily mean that these homes are particularly inefficient.…”
Section: Datamentioning
confidence: 97%
See 1 more Smart Citation
“…The most and least efficient dwellings are over-represented in our sample, at the expense of dwellings in EPC band C, while band B dwellings are represented fairly (and the most common category). It is unclear how this may affect the results, particularly as recent analysis has shown that EPC band is a poor predictor of energy use for bands C-G [77]. In general the SERL dataset struggled to be representative by dwelling and tenure type due to the uneven rollout of smart metering [50], and thus our sample is biased towards detached dwellings and owner-occupiers and under-represents flats/ apartments and renters.…”
Section: Fundingmentioning
confidence: 95%
“…We use the 6th edition Smart Energy Research Lab (SERL) [48][49][50][51][52] datasets comprising electricity, gas (where available), survey and weather data for around 13,000 homes in Great Britain. Initially households were removed from the sample who indicated having installed/replaced a heat pump or acquired an electric vehicle (EV) in the previous 12 months in the 2023 SERL Energy Survey (described below) as the predictive models are trained on the previous winter (before the heat pump installation or EV charging began/increased).…”
Section: Data Pre-processingmentioning
confidence: 99%